Nursing and medical care of child and adults with cardiopulmonary, glands and metabolism problem: a systematic review and meta-analysis - Fard, Maryam Adibzadeh; Sani, Somayyeh Ghorbani; Charmduzi, Forugh; Karimkoshteh, Azra; Hashemi, Parham; Danesh, Hoseinali (Bangladesh Journal of Medical Science, 2025)
Background and Rationale Heart disease is the leading cause of death worldwide. The goal of current study was to evaluate nursing and medical care of child and adults with cardiovascular disease. Methods 48 articles published until 2024 were reviewed with keywords including “Cardiopulmonary»,»Nursing»,» Medical Staff»,»Reconstructive Surgery» in PubMed, Web of Science, Scopus, Science Direct, Elsevier and Wiley. Results and Conclusion The results showed mean differences of cardiovascular risk score before and after nusing intervention declined 2.35 points (MD: -2.35 95% CI; -2.49, -2.20; p<0.01). Changes in the patient’s lifestyle can include smoking cessation, healthy diet, regular physical activity, weight control, blood pressure control, cholesterol and blood sugar control. BJMS, Vol. 24 No. 04 October’25 Page : 1246-1253